Intestinal parasites and HIV in Ethiopian tuberclosis patients: A systematic review and meta-analysis - Getenet Dessie, MSc; Ayenew Negesse, MPH; Fasil Wagnew, MSc; Desalegne Amare, MSc; Balew Zeleke Tiruneh, MSc; Henok Mulugeta, MSc; Berhanu Abebaw Mekonen, MPH; Dessalegn Haile, MSc; Tilksew Ayalew; Tesfa Dejenie Habtewold, PHD (Elsevier, 2020)
ABSTRACT: Background: The distribution of intestinal parasites among patients with tuberculosis in Ethiopia is not well understood. Objective: This systematic review and meta-analysis was designed to determine the pooled national prevalence of intestinal parasites and its association with HIV among patients with tuberculosis in Ethiopia. Methods: Original articles were searched in PubMed, Google Scholar, EMBASE, World Health Organization's HINARI portal, and supplemented by the hand searching of cross-references. Data were extracted using a standard data extraction checklist. Random-effects model was used to estimate the pooled prevalence of intestinal parasites and odds ratio of the association. The I2 statistic was utilized to quantify statistical heterogeneity across studies. Funnel plot asymmetry and Egger regression tests were used to check for publication bias. The analysis was done by STATA version 14 for Windows. Results: Of 725 identified studies, 12 articles were eligible for inclusion in the final analysis. The pooled national prevalence of intestinal parasites among patients with tuberculosis in Ethiopia was 36.1% (95% CI, 22.1-50.1; I2 = 98.7%). Subgroup analysis based on study design indicated that the prevalence of intestinal parasite among case-control studies was 41.69% (95% CI, 28.6-54.8; I2 = 95.1%). The odds of intestinal parasites among patients with tuberculosis-HIV coinfection was not significantly different compared with patients with tuberculosis without HIV/AIDS (odds ratio = 0.99; 95% CI, 0.7-4.7; P = 0.96). Conclusions: In Ethiopia, at least 1 out of 3 patients with tuberculosis have an intestinal parasite. These findings suggest a need of more attention on increasing screening tuberculosis patients for intestinal parasites and deworming interventions. (Curr Ther Res Clin Exp. 2020; 81:XXX-XXX)